Implementation of Neuro Nadi Method In Al-Qur’an Studies In Brunei: Implementasi Kaedah Neuro Nadi dalam Pengajian Al-Qur’an di Brunei - Jasni, Nurhamizah; Abdul Rahman, Mariam (Journal of Quranic Sciences and Research, 2022)
Neuro Nadi Method or known as Al-Baghdadi Method is a new method in the study of Qur’an in Brunei Darussalam. The diversity of forms and techniques in the study of Qur’an should be emphasized in order to increase the Qur’an reading among the community especially in Brunei. Therefore, surveys have been conducted on respondents studying using Neuro Nadi Method. Observations were also made to see its effectiveness in the study of Qur’an. The important elements have been discussed including the teaching techniques and aids used. Through positive effects and reactions from the respondents, Neuro Nadi Method in al-Qur’an studies that following the current teaching and learning will be able to help attract the people in this country to pursue the study of Qur’an and subsequently produce a generation who are morally noble and educated in the Qur’an studies.